2007
DOI: 10.1007/s11916-007-0009-7
|View full text |Cite
|
Sign up to set email alerts
|

Cluster headache in women

Abstract: Cluster headache has long been considered a predominantly male disorder, with much of our knowledge based on studies of men. However, it has become increasingly more recognized in women. Although there are many similarities between men and women in the expression of the disorder, studies over the years have revealed gender differences. This article reviews epidemiologic, clinical, hormonal, and familial differences between male and female cluster patients, examines how they may affect treatment, and suggests s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…However, under these premises, it may be hypothesised that genderrelated differences in illicit drug use is related to a more attenuated clinical expression of CH in women. Indeed, in our study bout frequency and bout duration were both significantly lower in the women than in the men, and isolated clinical descriptive studies from the literature have indicated that women with CH may not show exactly the same clinical and epidemiological characteristics as men with CH (19)(20)(21). Thus, in men, the phenotypic expression of CH may be accompanied by comorbid addictive behaviour leading to illicit drug use.…”
Section: Discussionmentioning
confidence: 44%
“…However, under these premises, it may be hypothesised that genderrelated differences in illicit drug use is related to a more attenuated clinical expression of CH in women. Indeed, in our study bout frequency and bout duration were both significantly lower in the women than in the men, and isolated clinical descriptive studies from the literature have indicated that women with CH may not show exactly the same clinical and epidemiological characteristics as men with CH (19)(20)(21). Thus, in men, the phenotypic expression of CH may be accompanied by comorbid addictive behaviour leading to illicit drug use.…”
Section: Discussionmentioning
confidence: 44%
“…Regarding patient gender distribution, most of our patients were males, in coincidence with the findings in the literature (12). However, according to Manzoni (13), the male predominance is gradually decreasing – possibly as a result of changes in lifestyle in both sexes, particularly in women (14). …”
Section: Discussionmentioning
confidence: 99%
“…CH is commonly considered a disorder of young men although it is increasingly also seen in middle aged and elderly women 3 , 4. The male:female ratio for this illness is 5:1 5 , 6.…”
Section: Discussionmentioning
confidence: 99%
“…The cluster attacks occur with striking periodicity, from once every other day up to eight times a day and usually last 15 to 180 min. There is an episodic form that is more common while the chronic form is relatively rare 3. The diagnosis is made on clinical grounds.…”
Section: Discussionmentioning
confidence: 99%